(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article studies the concept of “military terminology” in modern Russian. The relevance of the study is due to the widespread use of military terminology in the media and the rapid advancement of weapons technology. The aim of our research is to study the features of military terminology in modern Russian. The research methods are: the study of scientific literature on the topic, the analysis and the classification. The article distinguishes between the concepts of “military vocabulary” and “military terminology”, defining military terminology as a significant part of military vocabulary. The article explores the problem of studying military terminology in a historical context and analyzes various modern approaches to the classification of military terms concluding that these classifications have a number of shortcomings. The novelty of the study lies in the expansion and deepening of the existing classifications of military terminology. The system of military terms is quite mobile: old terms are replaced by new ones, and many foreign borrowings appear. The article concludes that military terminology occupies a significant place in the lexical system of the language, it is widely used in everyday speech of native speakers and in journalism. The study of military terminology is of great importance not only within the framework of linguistics, but is also of high value for history.